1994
DOI: 10.1093/nar/22.3.419
|View full text |Cite
|
Sign up to set email alerts
|

Context effects on N6-adenosine methylation sites in prolactin mRNA

Abstract: The methylation of internal adenosine residues in mRNA only occurs within GAC or AAC sequences. Although both of these sequence motifs are utilized, a general preference has been noted for the extended sequence RGACU. Not all RGACU sequences in an mRNA are methylated and the mechanisms that govern the selection of methylation sites in mRNA remain unclear. To address this problem we have examined the methylation of transcripts containing sequences of a natural mRNA, namely, bovine prolactin mRNA. In this mRNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 29 publications
4
47
0
Order By: Relevance
“…The amount of m 6 A in isolated RNA is estimated to constitute 0.1–0.4% of all adenosine nucleotides in mammals 18,28 , 0.7–0.9% of adenine nucleotides (all within GA dinucleotides) in meiotic Saccharomyces cerevisiae 29 , and 1–15 sites per virion RNA molecule in various viruses 30 . Mutation and in vitro enzymatic studies have identified a consensus motif of RRm 6 ACH ([G/A/U][G>A]m 6 AC[U>A>C]) 3134 . However, owing to the low abundance of m 6 A in mRNA and the lack of effective techniques, functional characterizations of m 6 A have been largely absent over the past few decades.…”
mentioning
confidence: 99%
“…The amount of m 6 A in isolated RNA is estimated to constitute 0.1–0.4% of all adenosine nucleotides in mammals 18,28 , 0.7–0.9% of adenine nucleotides (all within GA dinucleotides) in meiotic Saccharomyces cerevisiae 29 , and 1–15 sites per virion RNA molecule in various viruses 30 . Mutation and in vitro enzymatic studies have identified a consensus motif of RRm 6 ACH ([G/A/U][G>A]m 6 AC[U>A>C]) 3134 . However, owing to the low abundance of m 6 A in mRNA and the lack of effective techniques, functional characterizations of m 6 A have been largely absent over the past few decades.…”
mentioning
confidence: 99%
“…Studies in the 1970s revealed that m 6 A modification in mRNA mainly occurs at Pu[G > A]m 6 AC[U > A > C] (Pu represents purine) and is estimated to be present at an average level of approximately three m 6 A residues per mRNA Narayan and Rottman 1988;Csepany et al 1990;Narayan et al 1994). Transcriptome-wide mapping of m 6 A is hindered by the following two facts: (1) m 6 A, akin to A, reverse-transcribes to a thymine (T), and (2) m 6 A is not susceptible to chemical modifications that might promote its detection.…”
Section: Features Of M 6 a On A Global Scalementioning
confidence: 99%
“…The only cellular mRNA for which individual m 6 A sites have been mapped is that encoding bovine prolactin (bPRL) (Horowitz et al 1984;Narayan et al 1994). Unlike viral mRNA, labeling steady-state mRNA populations in eukaryotic cells with 32 P-orthophosphate or [ 3 H-methyl]methionine results in the incorporation of low amounts of radioactivity into individual mRNAs.…”
Section: A In Vivomentioning
confidence: 99%
“…A rapid assay for m 6 A formation and the development of an in vitro system for studying m 6 A formation in nuclear extracts facilitated the study of this methyltransferase (Narayan and Rottman 1988;Narayan et al 1994;Bokar et al 1994). Briefly, a synthetic RNA substrate of 60 nucleotides of the 3'-terminus of bovine prolactin mRNA was used as a substrate for methyl transfer from [ 3 Hmethyl]AdoMet.…”
Section: Characterization and Purification Of Hela Mrna N 6 -Adenosinmentioning
confidence: 99%